Association between the RETN -420C/G polymorphism and type 2 diabetes mellitus susceptibility: A meta-analysis of 23 studies - Luo, Fei; Shi, Mingjie; Guo, Junhao; Cheng, Yisen; Xu, Xusan; Zeng, Jieqing; Huang, Si; Huang, Weijun; Wei, Wenfeng; Wang, Yajun; Chen, Riling; Ma, Guoda (Frontiers in Endocrinology, 2022)
Background The published findings on the link between the resistin (RETN) gene polymorphism and type 2 diabetes mellitus (T2DM) risk are still contradictory. Here, through a meta-analysis, we summarized a more precise evaluation of their connection by synthesizing existing research. Methods PubMed, Google Scholar, and Web of Science were electronically searched, and all cited sources were manually searched. The heterogeneity of effects was tested and all statistical analyses were performed in Stata 12.0. Results A total of 23 studies with 10,651 cases and 14,366 controls on RETN -420C/G polymorphism were included. The overall results showed that the association of RETN -420C/G polymorphism and T2DM susceptibility was not significant [for the allelic model: odds ratio (OR) = 0.98, 95% confidence interval (CI) = 0.87–1.10, pheterogeneity <.001; I2 = 84.6%; for the dominant model: OR = 0.96, 95% CI = 0.80–1.15, pheterogeneity <.001; I2 = 87.1%; and for the recessive model: OR = 0.96, 95% CI = 0.82–1.12, pheterogeneity <.001; I2 = 56.9%] but with high heterogeneity across studies (p <.0001). Meta-regression found that the median age of T2DM participants (using age 50 as the cutoff) could be a factor in the observed variation. The RETN -420C/G polymorphism seems to be linked to an increased risk of T2DM in younger individuals [for dominant: OR = 0.84 (95% CI, 0.72–0.98; pheterogeneity <.001; I2 = 80.9%)] and decreased risk in older people [for dominant: OR = 3.14 (95% CI, 2.35–4.19; pheterogeneity = .98; I2 = 0.0%)]. Conclusions Current results found no evidence that the RETN -420C/G variant was linked to T2DM susceptibility, but the patient’s age appears to be a potential factor that contributed to high heterogeneity across studies. Additional high-quality and well-designed investigations are required to confirm these results.